ANALYSIS OF PRODUCT QUALITY, PRICE, PROMOTION AND BRAND IMAGE OF IPHONE PHONES ON PURCHASING DECISIONS - Risang Prasana, Duannaja Octa; Wiyadi (Sekolah tinggi ilmu ekonomi pemuda, 2024)
The purpose of this study was to analyze product quality, price, promotion and brand image of iphone phones on purchasing decisions. This research method is quantitative. The data source for this research is primary data. The population in this study were all people who used iphone phones. In this study using nonprobability sampling techniques with Incidental Sampling techniques. Nonprobability Sampling. The number of samples in this study were 210 respondents. The data analysis technique used in this research is descriptive analysis and Structural Equation Model (SEM) analysis with Smart Partial Least Square (PLS). The result of this study is that product quality has no effect on purchasing decisions. Price also has no effect on purchasing decision variables. Promotion has a positive and significant influence on purchasing decisions. Brand image has a positive and significant influence on purchasing decisions.